Development of Smart Servers for Informatics Education Program Using NDLC Method - Jamaluddin, Jamaluddin; Muhammad Zamroni Uska; Wirasasmita, Rasyid Hardi; Roziki , Muhammad (Universitas Medan Area, 2024)
The development of processor technology, especially Multicore Processors, has had a significant impact in various fields, including the field of higher education, one of which is the need for Virtual Private Servers for information management and their potential as a storage space for web development products. This research aims to create a Virtual Private Server in the Informatics Education program at the Faculty of Mathematics and Natural Sciences of Hamzanwadi University. It uses the Research & Development (R&D) method with the Network Development Life Cycle (NDLC) approach, involving six stages: Analysis, Design, Prototype Simulation, Implementation, Monitoring, and Management. Data were obtained through interviews and questionnaires, then analyzed descriptively qualitatively. The research resulted in a Virtual Private Server using Proxmox VE 7.4, Ubuntu 18.04.5 operating system, remote access via OpenSSH-Server, Control Panel AAPanel 6.8.30, Nginx 1.21.4 web server, MySQL 5.7.34 database management system, PHP 7.4, PhpMyAdmin 5.0 for web access to the database, and PureFTPd 1.1.49 as the FTP Server. Expert evaluations in the field of IT yielded a rating of 83% with the category